Examining early learners’ perceptions of inclusion: adaptation of the student version of the perceptions of inclusion questionnaire for first- and second-grade students (PIQ-EARLY) - Grüter, Sandra; Goldan, Janka; Zurbriggen, Carmen L. A. (Frontiers in Psychology, 2023)
Promoting the emotional and social development of students with and without special needs is a central goal of implementing inclusive education in the school system. The entry into school, and thus into the formal education system, is accompanied by emotions and changes in self-image and social relationships. For assessing emotional inclusion, social inclusion, and academic self-concept, the Perceptions of Inclusion Questionnaire (PIQ) is a widely used instrument. To date, the paper-pencil questionnaire has been used from third through ninth grades but has not yet been used with younger ages. This paper presents an adapted version of the PIQ for first- and second-grade students, which was used on two measurement time occasions (T1, N = 407, MAge = 7.2; T2, N = 613, MAge = 7.6). Information on students’ reading and listening comprehension was collected from the class teachers to verify whether the adapted questionnaire can be used for all students with different levels of language competencies. Measurement invariance was demonstrated to be at least scalar for all groups considered in the analyses. Students with higher rankings of reading and listening comprehension skills reported significant higher levels of emotional inclusion and academic self-concept while there were no significant differences in social inclusion. The findings suggest that the PIQ-EARLY is a suitable instrument for assessing self-perceived inclusion in first- and second-grade students. The results also highlight the importance of students’ language competencies for adjustment to school in early school years.